PERBANDINGAN KEBUTUHAN CAIRAN DAN PEMBIAYAAN DALAM PROSES PERAWATAN ULKUS KAKI DIABETES MELITUS DENGAN METODE PENCUCIAN LUKA 13 PSI DAN 7 PSI - Heri Kristianto (Department of Nursing, Faculty of Health Sciencce, Universitas Brawijaya, 2016)
Betaine Polyhexanide (PHMB) is often being used as wound cleansing solution in current clinical practice for wound care. betaine polyhexanide (PHMB) can reduces the surface tension of the biofilm. The aim of this study was to compare the need of betaine plyhexanide (PHMB) solution and the cost effectiveness in the treatment of diabetic foot ulcers using cleansing method of 13 psi and 7 psi. The observation was conducted for 6 days at Fatmawati Hospital in Jakarta on 18 samples of diabetic foot ulcers. The data were analyzed using SPSS version 15.0. The results of this study showed that the need of betaine polyhexanide (PHMB) solution and the cost effectiveness of irrigation pressure method of 13 psi is more effective and more efficient than the irrigation method of 7 psi ( p = 0.006 ; p = 0:02 ; CI 95 % ). The combination of irrigation pressure method of 13 psi using 0.9 % NaCl and betaine polyhexanide (PHMB) is recommended in clinical applications.Keywords: irrigation pressure, 13 psi, 7 psi, prontosan®, diabetic foot ulcer